Frontiers in science and technology - Yunus, Kamaruzzaman (IIUM Press, International Islamic University Malaysia, 2017)
INTRODUCTION The intention of “ Frontiers of Science and technology” is to provide an absolutely introductory yet rather systematic and comprehensive textbook tailored to the interests of the broader audience of science, technology, and medicine. This book is written by a number of active researchers in various scientific disciplines research experiences in science which is mostly interdisciplinary and multidisciplinary in nature.